STEREOTIP GENDER DALAM FILM CHAOS WALKING - Imma Latifa (KRONIK : Journal of History Education and Historiography, 2022)
Movies are one of the media for the social construction of society regarding various issues in many lines of life. One of them is gender stereotypes which has always been an interesting topic of discussion, especially in a strong patriarchal environment. This study uses the movie Chaos Walking (2013) by Doug Liman as the object of research. The purpose of this study is to find out how gender stereotypes are formed and represented in this movie. This study uses a qualitative research method with the semiotic method by Roland Barthes. Qualitative data in this study were obtained through documentation, which is movie. The results obtained are as follows: (1) men are represented as individuals who must behave masculine, strong, and powerful. (2) women’s existence are unnecessary. (3) men become manipulative individuals even among men. (4) the Chaos Walking movie shows the existence and role of men and women as important to interact and coexist. (5) Chaos Walking movie constructs gender stereotypes through dialogue, behavior, and visualization in the movie.